(untitled) (Open Herald: Periodical of Methodical Research, 2024)
Earlier to sowing seeds of rural crops, mindfulness of the warm, water, and light administrations of the arrive is of extraordinary significance. In this article, we examined the warm and temperature conditions of level and slanted lands through the warm exchange conditions within the soil. At the same time, the temperature invariance at a certain profundity from the soil surface was primarily gotten, on the premise of which an equation for calculating the soil temperature from the dregs was inferred by the strategy of consonant investigation. In expansion, equations for level Arrive and temperature administrations of 10˚, 20˚, 30˚ inclines relative to the skyline for southern and northern surfaces have been discharged. Hypothetical calculations have appeared that the temperature on the inclines is higher than on the level lands compared to the test comes about. This recommends that rural specialists are making conditions for sowing plant seeds within the ground in early spring.